2009
DOI: 10.1080/15622970802688069
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit juice alters plasma sertraline levels after single ingestion of sertraline in healthy volunteers

Abstract: These results suggest that grapefruit juice affects the pharmacokinetics of sertraline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…A recent study has found that grapefruit juice (a known inhibitor of CYP3A4, CYP1A2 and P-glycoprotein) causes a 70% increase in SRT C max and a 100% increase in its AUC 0--¥ [96]; however, these data were obtained from healthy volunteers after a single SRT dose and their clinical significance, if any, has not been evaluated.…”
Section: Safety and Tolerabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study has found that grapefruit juice (a known inhibitor of CYP3A4, CYP1A2 and P-glycoprotein) causes a 70% increase in SRT C max and a 100% increase in its AUC 0--¥ [96]; however, these data were obtained from healthy volunteers after a single SRT dose and their clinical significance, if any, has not been evaluated.…”
Section: Safety and Tolerabilitymentioning
confidence: 86%
“…On the other hand, citalopram, venlafaxine, mirtazapine and reboxetine seem to be in turn safer than SRT due to their very weak inhibition of CYP isoforms [106]. Table 2 reports a list of possible significant SRT interactions; it includes only those interactions that are reported in the FDA-approved labeling [29] and/or are based on clinical studies [70,71,96,[107][108][109][110].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Our findings are largely in line with what could be expected from in vitro and in vivo data on which PPIs being the most potent inhibitors of CYP2C19 11 15 and which SSRIs that to the largest extent are dependent on CYP2C19 in their metabolism. 2 – 7 Specifically, omeprazole and esomeprazole have been found to be more potent CYP2C19 inhibitors than lansoprazole and pantoprazole, 11 15 with esomeprazole and omeprazole having about the same inhibiting potential. 11 The more pronounced effect on the C/D ratio for escitalopram than for citalopram is consistent with the fact that CYP2C19 seems to be even more important in the metabolism of S-citalopram than of R-citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…In the Li et al (3) study, cited by Dr. Dentali, gingko biloba purchased from pharmacies in Chicago did not reveal any significant colchicine levels. Several sources were cited in the review regarding the potential for increased risk for bleeding (references 4,5,8,9,[32][33][34]43, and 49 in the review). The information on the neonatal death is from a monograph on ginseng prepared by the Natural Standard Research Collaboration (13) and is available at the Medline Plus website, a service of the U.S. National Library of Medicine and the National Institutes of Health.…”
Section: Replymentioning
confidence: 99%
“…The study cited by Dr. Asher (Shimada et al [32]) immunochemically characterized CYP in 60 patients and found CYP 3A4 to represent about 30% of total CYP, but those investigators did not assess the proportions of drugs metabolized by various subtypes of CYP enzymes. With regard to sertraline, we would like to bring to the attention of Dr. Asher a study by Ueda et al (34) using a crossover design in healthy subjects given grapefruit juice or water and then sertraline 75 mg on day 6, demonstrating a significant increase in mean peak plasma sertraline concentration (from 17.6 Ϯ 6.1 to 29.3 Ϯ 11.5 ng/ml) and the mean area under the plasma sertraline concentration-time curve from zero to infinity of sertraline from 402 Ϯ 152 to 820 Ϯ 313 h·ng/ml. In our review, we emphasized that caution be taken when compounds that can significantly affect the activity of CYP 3A4, when coadministered with substrate of this enzyme, because it can result in elevated blood levels.…”
Section: Replymentioning
confidence: 99%